Is therapeutic plasma exchange effective in leptospirosis-associated severe pulmonary haemorrhagic syndrome? A systematic review - Bandara, J M R P; Rosairo, A; Ranasinghe, G S; De Silva, T D; Gawarammana, I B (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2025)
Leptospirosis is a re-emerging zoonosis fast becoming a global burden. Pulmonary haemorrhages are a deadly complication, with case fatality rates >50%. Systemic vasculitis is thought to be the pathological process responsible for pulmonary haemorrhages and therapeutic plasma exchange (TPE) is one of the treatments offered. This systematic review aims to evaluate the effectiveness of TPE in managing leptospirosis-associated severe pulmonary haemorrhagic syndrome (SPHS). A systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis protocol. The search used Medical Subject Headings in PubMed with keywords ‘Leptospirosis’ OR ‘Leptospira’ OR ‘Weil disease’ AND ‘plasmapheresis’ OR ‘plasma exchange’ AND ‘pulmonary haemorrhage’ OR ‘alveolar haemorrhage’. The search was widened to include the Google Scholar database. The review was confined to English-language articles and focused on primary research studies. Nineteen articles were considered for analysis. There were no randomized controlled trials. A non-randomized trial and a retrospective cohort documented recovery following adjuvant TPE treatment. Most case reports mention significant improvement and complete recovery following administration of TPE. One case reported the death of a patient despite treatment. However, this review revealed a lack of strong evidence endorsing the routine application of TPE as a therapeutic intervention for cases of SPHS. Thus we recommend the initiation of a well-structured randomized controlled trial to ensure an accurate assessment of the efficacy of TPE.